2005
DOI: 10.1007/s00423-005-0562-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of neoplastic foci and lymph node micrometastasis within the mesorectum

Abstract: Combination of large tissue slice and tissue microarray provided a more detailed method in studying the metastasis of rectal cancer. Complete excision of the mesorectum with fascia propria circumferentially intact is essential. Circumferential margin involvement and micrometastasis suggested that tumor spread may go beyond the scope of a single TME procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 23 publications
(23 reference statements)
0
42
0
Order By: Relevance
“…5 mm in diameter are more often involved by the tumor than bigger ones. Such findings pinpoint the importance of TME [24][25][26] . The pathologist must differentiate the peritonealized from non-peritonealized surfaces of the resection.…”
Section: Circumferential Resection Marginmentioning
confidence: 70%
“…5 mm in diameter are more often involved by the tumor than bigger ones. Such findings pinpoint the importance of TME [24][25][26] . The pathologist must differentiate the peritonealized from non-peritonealized surfaces of the resection.…”
Section: Circumferential Resection Marginmentioning
confidence: 70%
“…A small T1 tumor has a 15% risk of lymph node (LN) involvement and T2 a 25% risk of LN involvement, but these nodes are likely to be close to the primary tumor [36]. Current evidence suggests that 90% of involved lymph nodes lie within 2 cm superior to the macroscopic tumor on MRI [75].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for cT2 tumors 58/194 (30%) had N1 and 14 (7%) had N2 nodal disease, but only 8/194 (4%) had lymph node metastases beyond the pararectal mesorectum. Descriptions of mapping of sites of lymph nodes within the mesorectum in more advanced stages are sparse and performed on few patients [36].…”
Section: Mesorectal Lymph Nodes In Surgical Seriesmentioning
confidence: 99%
“…First, Wang et al reported that many as 94% of involved nodes may be smaller than 5 mm (20) ; thus, although we utilized a cut-off size of 5 mm, metastases of ≤5 mm could not be identi!ied using this technique. CT cut-offs of 2 or 3 mm would presumably result in higher NPV, and thus more strongly to support our observations.…”
Section: "Watchmentioning
confidence: 99%